Temporal variations in biomass and size of seabob shrimp Xiphopenaeus kroyeri (Heller, 1862) (Decapoda: Penaeoidea) on the southern coast of São Paulo state, Brazil - Miazaki, Lizandra Fernandes; Santos, Ana Paula Freitas Dos; Salvati, Dalilla Da Silva; Alves-costa, Fernanda Antunes; Costa, Rogério Caetano Da (Sociedade Brasileira de Carcinologia, 2016)
Abstract Xiphopenaeus kroyeri (Heller, 1862) is the third most common species caught by fishing boats in the state of São Paulo, Brazil and production of this shrimp in the Cananéia region located on the southern coast of this state ranks second in the nation. The aim of this study was to investigate the temporal variation of the total biomass and size of X. kroyeri and analyze this variation against environmental factors in order to suggest some information about the best periods to fish this species. Samples were caught monthly from four sampling stations in Cananéia between July 2012 and June 2014 using a fishing boat equipped with otter-trawl nets. Temperature and salinity were monitored using a multiparameter probe, and sediment samples were also taken using a Van Veen-type gripper for particle size analysis. The shrimp were weighed, quantified, and carapace length was measured (mm). In general, the highest total biomass values were recorded when the fishery was closed in the southeast and south regions, and the highest catch of smaller individuals was also observed during this period. In contrast, in November 2013 the fishing is permitted and high biomass composed of large individuals was observed. The monthly biomass showed a positive relationship with sediment texture, because this species prefers very fine sediments to burrow as a defense against predators.
Keywords: Abundance; closed season; fishery; Penaeidae; weight